PENERAPAN KONSEP SOCIAL SUSTAINABILITY PADA RUMAH TINGGAL ORANG MINANGKABAU PERANTAUAN: The Application Of Social Sustainability Concept In The House Of The Overseas Minangkabau People - Resky Annisa Damayanti; Elda Franzia Jasjfi; Atridia Wilastrina; Jelly Tan; Rosidianti Alifah (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
The culture of gathering is still practiced by the Minangkabau people, both those who still live in hometowns and those who have migrated. A number of traditions are still carried out by Minangkabau people today. The culture and traditions must be maintained and preserved for the sake of social interaction (social sustainability). The concept of social sustainability is a link between design of the physical world and social world, which means that although comfortable housing is important, residential design that is able to maintain social relations, social networks, and cultural development must also be considered. This study aims to classify zoning and grouping to produce recommendations for layouts. That way, the scope of interior design in solving residential problems is expected to be solved systematically so as to produce a layout that facilitates the needs of its inhabitants. The method used is qualitative with cultural approach (cultural studies) to describe spatial divisions in residential houses based on cultural activities of the overseas Minangkabau people. Data was collected using documentation and interviews. The findings of this study are related to spatial arrangements in the house of the overseas Minangkabau people in providing space to fulfill the activities carried out by Minangkabau people today. The layout of the overseas Minangkabau people has a shape in the front has an area of ​​space that can accommodate the number of residents and relatives of same clan. This research is able to become the basis for criticism and evaluation for developers to design housing in the future.